Studies of the voltammetric behavior and determination of diazo reactive dyes at mercury electrode - Guaratini, CCI; Fogg, A. G.; Zanoni, Maria Valnice Boldrin [UNESP] (Wiley-Blackwell, 2001)
The electrochemical reduction of two reactive dyes: Procion Red HE-3B 9 (RR120) and Procion Green HE-4BD (RG19) was investigated using cyclic voltammetry, differential pulse and DC, polarography, chronoamperometry and controlled potential electrolysis at mercury electrodes. The bis-azo groups of the RR120 dye are reduced together in one single step of four electrons, the bis-azo groups of the RG19 dye are reduced in two steps owing to the difference in the electron densities promoted by the different substituents in the benzene rings adjacent to the azo groups. The bis-monochlorotriazine reactive groups in both dyes are reduced only in acidic medium in their protonated form, leading to the reduction of the triazine groups. The reduction mechanism of both reactive dyes is discussed. Both dyes can be quantified in aqueous medium by differential pulse polarography in the concentration range of 1 x 10(-7) mol L-1 to 1 x 10(-5) mol L-1 by monitoring the reduction of the chromophore group or the reactive group.
Keywords: reactive dyes; electrochemical reduction; Procion Red HE-3B; Procion Green HE-4BD